Amalan Baik: Pengurusan Sisa Binaan - Muhamad Jais, Nor Elliya Hazuwani; Shareh Musa, Sharifah Meryam; Abd Rahim, Mohd Hilmi Izwan; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2023)
The construction industry is one of the industries that contribute to the national economy. However, the construction industry is also a contributor to environmental pollution. The problem for this study is the unsystematic management of construction waste where it is not disposed of in the right way. The objective of this study is to identify good environmental practices of construction waste management that contribute to sustainable construction, identify obstacles that cause environmental good practices of construction waste management cannot be implemented and suggest methods for improving environmental practices of construction waste management at   construction sites. Research methods that use primary data and secondary data. For primary data, a qualitative method through semi-structured interviews was conducted while for secondary data, a literature review method was used where all information was obtained from journals, articles, books and seminar papers. Next, this study involved 5 respondents from G7 contractors in the state of Selangor. The data obtained from the results of interviews with respondents were analyzed using content analysis. The results of the study obtained based on the first objective are that all respondents are sensitive and have knowledge related to construction waste management and how to select materials. For the second objective, some of the respondents have experienced obstacles related to time and need to pay attention to the issue of obstacles. While for the third objective, all respondents agreed that IBS, BIM and the 3R method are able to reduce the generation of waste at the construction site as well as minimize the impact on the environment. In conclusion, all parties directly involved in the construction site need to be responsible and aware of the importance of systematic construction waste management to ensure waste generation can be reduced and minimize the impact on the environment and local residents.